Investigating lattice vibrational and excitonic properties of two-dimensional heterostructures of transition metal dichalcogenides - Wu, Lishu (Nanyang Technological University, 2021)
Atomically thin transition metal dichalcogenides (TMDs) with suitable bandgaps are becoming the new generation of two-dimensional (2D) semiconductors, which open many opportunities to bring conventional electronic and optoelectronic applications based bulk semiconductors down to the monolayer limit. Their covalently bonded lattice and weak van der Waals (vdWs) interactions enable the possibility to isolate and reassemble highly diverse atomic layers into varieties of vdWs heterostructures with novel intriguing material properties and promising application prospects. Thus, studying their lattice vibrational and excitonic properties is fundamentally necessary and important. In this thesis, we focus on optical studies on three types of TMD heterostructures by Raman and photoluminescence (PL) micro-spectroscopic techniques and are particularly interested in interlayer interactions and valley magnetic effects. First, twisted vdWs homo- and hetero-structures have aroused great attentions due to their unique physical properties, providing a new platform to explore 2D condensed matter physics. However, the effects of twist angle on lattice vibration in the TMD heterostructures are still elusive. Here, in the twisted WS2/MoS2 heterostructures, distinct evolutions of Raman scattering as well as the underlying interlayer interactions have been found to be sensitive to the twist angle, which has been interpreted in terms of the interplays of interlayer mechanical coupling and charge transfer. The frequency separations between E2g and A1g modes of MoS2 and WS2 in the twisted heterostructures vary with the interlayer mechanical coupling, essentially originating from the spacing-related repulsion between sulfur atoms. Moreover, the opposite shift behaviors and broadening of A1g modes mainly result from charge transfer. The calculated interlayer distances and band alignment of twisted WS2/MoS2 through density functional theory (DFT) further evidence our interpretations on the roles of the interlayer mechanical coupling and charge transfer in variations of Raman features. Secondly, the unique valleytronic properties of TMDs enable many device applications with the additional valley degree of freedom while considerable valleytronic properties of the emerging TMD alloys and their heterostructures with tunable bandgaps remain largely unexplored. Here we observe strong valley Zeeman effect of negatively charged excitons or trions in a TMD alloy (i.e., monolayer Mo0.5W0.5Se2) and its heterostructures (i.e., Mo0.5W0.5Se2/WS2) studied by low-temperature valley-resolved magneto-PL micro-spectroscopy. In the aspect of fundamental quasiparticles, we performed a focus study on valley Zeeman effect of the negatively charged excitons (i.e., three-body problem) rather than excitons (i.e., two-body problem). Beyond the successful formation of the type-II alignment of TMD alloy heterostructures, we further investigate the interlayer coupling effect on valley magnetic response of vdWs heterostructures. In Mo0.5W0.5Se2 and Mo0.5W0.5Se2/WS2 heterostructures, the large g factors of negatively charged excitons of 8.3 and 7.0 were respectively extracted, which were caused by doping-induced strong many-body Coulomb interactions. Moreover, the relatively reduced trion valley splitting in Mo0.5W0.5Se2/WS2 is a consequence of the weakened exchange interaction arising from p-doping in Mo0.5W0.5Se2 via interlayer charge transfer. Such interlayer charge transfer further evidences the formation of type-II band alignment and is consistent with the DFT calculations. Thirdly, studies on the valley Zeeman effect of MoS2 monolayers and their heterostructures are still under debate, which are mainly limited by the broad linewidth and the overlapping of few emission components of as-exfoliated MoS2 monolayers. Moreover, the magnetic response of higher excitonic states and exciton complexes of MoS2 monolayers and their heterostructures is less explored. Here we present the systematic investigation of valley magnetic response of Rydberg excitonic states and exciton complexes in high-quality hBN/MoS2/hBN heterostructures. Unlike the previous valley Zeeman studies on MoS2, we have made the advances in determination of valley Zeeman splitting of 2s and 3s A excitons by the magneto-luminescence geometry and observations of extraordinary valley magnetic response of exciton replica and dark excitons. The g factors of 1s, 2s and 3s A excitons are found to be dependent on the principal quantum number. An unconventional positive g factor is determined for the first-order phonon replica, which is attributed to the inversion of the photon helicity with the strong in-plane exciton-phonon coupling. Furthermore, the observed anomalous valley Zeeman response with the negligible splitting has been correlated with dark exciton states.